2016
DOI: 10.1111/cea.12738
|View full text |Cite
|
Sign up to set email alerts
|

Severe or life‐threatening asthma exacerbation: patient heterogeneity identified by cluster analysis

Abstract: SummaryBackground Severe or life-threatening asthma exacerbation is one of the worst outcomes of asthma because of the risk of death. To date, few studies have explored the potential heterogeneity of this condition.Objectives To examine the clinical characteristics and heterogeneity of patients with severe or life-threatening asthma exacerbation.Methods This was a multicentre, prospective study of patients with severe or life-threatening asthma exacerbation and pulse oxygen saturation < 90% who were admitted t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 61 publications
1
20
0
1
Order By: Relevance
“…Cluster analyses are being brought to bear on more complex clinical issues. In this paper, Seikiya et al confirm previous observations that severe asthma exacerbations arise in clusters with underlying severity, in those with multiple comorbidities especially among women, those not using ICS and interestingly among symptomatically mild patients who had had a previous hospital admission for asthma, one of the strongest predictors of severe exacerbations …”
Section: Asthma and Rhinitissupporting
confidence: 84%
See 1 more Smart Citation
“…Cluster analyses are being brought to bear on more complex clinical issues. In this paper, Seikiya et al confirm previous observations that severe asthma exacerbations arise in clusters with underlying severity, in those with multiple comorbidities especially among women, those not using ICS and interestingly among symptomatically mild patients who had had a previous hospital admission for asthma, one of the strongest predictors of severe exacerbations …”
Section: Asthma and Rhinitissupporting
confidence: 84%
“…In this paper, Seikiya et al confirm previous observations that severe asthma exacerbations arise in clusters with underlying severity, in those with multiple comorbidities especially among women, those not using ICS and interestingly among symptomatically mild patients who had had a previous hospital admission for asthma, one of the strongest predictors of severe exacerbations. 109 In a longitudinal study of severe poorly controlled asthma, Walsh et al 110 showed that sputum eosinophilia (but not sputum neutrophilia) is a strong predictor of asthma exacerbations. This supports the clinical experience with these severe allergic patients.…”
Section: Severe Asthmamentioning
confidence: 99%
“…Asthma creates a large burden on society including high societal costs . It can reduce quality of life of patients, increase the rate of morbidity and co‐morbidity, and can be life‐threatening . Worldwide about 250 000 deaths are attributed to asthma annually .…”
Section: Introductionmentioning
confidence: 99%
“…While there is important progress in characterizing patients with asthma in relation to endotypes and genotypes revealing potential pathways overlapping with ARC46, there is still a long way to go in this research area as none of the previous cluster analyses or phenotypic characterization studies included ARC as a phenotype of asthma138139140141142143144145146147148149150151152153154. We believe that studying the mechanistic pathways underlying the association between asthma and the risk of RA or other ARC may advance our understanding of the nature of asthma and ARC, and it will ultimately benefit scientists and clinicians in understanding the nature of chronic proinflammatory diseases by providing insight into the diseases.…”
Section: Discussionmentioning
confidence: 99%